Emarketing for wine tourism - Cravidão, Mário (2013)
This research aims to identify the main features in Wine Tourism operators' websites and to present a suggestion on how these operators could maximize the Internet tool. Ultimately, this research intends to assess the use of eMarketing for Wine Tourism. The sampled websites belong to six important wine producers in Portugal. Through the content analysis of the websites, we sought to determine the popularity and visibility of these, as well as their performance in categories such as Basic Information, Visual Information, Societal Information, Virtual Information, Trustworthy Information, Website Navigation, Customer Relations and Sales. Also, an email was sent by a Mystery Customer, similar to the widely used technique in Retail, in order to assess the quality of service for online customer, namely time and quality of reply. The results show that companies have not yet realized the full potential of eMarketing. Some suggestions are presented to maximize that tool in order to gain a competitive advantage.